Análisis de la cartera de crédito y formulación de estrategias para reducir el riesgo crediticio en la cooperativa de ahorro y crédito “servidores municipales de Loja” Ltda., periodo 2013-2017 - Cabrera Zaruma, Andrea del Cisne (2018)
The present work of Thesis called. "ANALYSIS OF THE CREDIT PORTFOLIO AND FORMULATION OF STRATEGIES TO REDUCE THE CREDIT RISK IN THE SAVINGS AND CREDIT COOPERATIVE" SERVIDORES MUNICIPALES DE LOJA "LTDA., IN THE 2013-2017 PERIOD", was developed with the purpose of carrying out an evolutionary analysis of the credit portfolio, as well as the application of indicators that allowed the identification of possible credit risks, and in this context formulate strategies to reduce them; fulfilling the objectives set out in the research work. The first objective began with the compilation of information about the cooperative regarding its background (historical review, mission, vision, values, principles and the structural organization chart), collection of financial statements from 2013 to 2017 of the Cooperative in This study analyzed the evolution of the loan portfolio to determine which factors caused an increase or decrease, and whether these had an impact on the effective performance of the institution. In the application of the indicators, it was determined if the cooperative is under the established standards, which help to reduce the credit risk and prompt recovery of the portfolio and that it generates resources towards the institution. Finally, strategies based on the SWOT analysis were formulated using techniques such as the survey and interview applied to the manager, staff and partners of the entity for a better appreciation of the strengths, weaknesses, opportunities and threats, which will allow to counteract affectations to the financial structure and growth within the market.